The Strength of Natural Disaster Local Wisdom in Indonesian and Japanese with Story Telling Approach - Damayanti Wardyaningrum; Nina Alia Ariefa (UniversitasAl Azhar Indonesia, 2025)
Indonesia and Japan are two countries that have things in common especially form natural disaster vulnerability and tsunami. There are various efforts conducted by government of both countries to mitigate disaster risk. People of Indonesia and Japan who live in a prone disaster area still own a sense of local wisdom by believing in myths concerning natural disaster. The purpose of this research is to identify myths in local wisdom regarding earthquacke and tsunami in Indonesia and Japan throught the six elements approach from storytelling concepts, namely: emotion, plot, structure, hero, villain and conflict. The research method use qualitative approach with text analysis to a number of sources and supported by interviews. Result shows that the myths believed by Indonesian is related to background of tsunami that happened because of the mystical life underwater ruled by the legend Ratu Kidul. While for Japanese, they believe that the cat fish called Namazu was the reason behind earthquake. The local wisdom has meaning in regards with the history of massive natural disaster event, the ability of local people in reading nature’s signs, alertness toward nature’s bigger power, the effort for asking God’s guidance and tradition in building group power within local society.Keywords - Indonesia, Japan, Local Wisdom, Natural Disaster, Storytelling.